Coordination in the Corruption Eradication Commission (KPK)'s Prosecution Tasks Based on Independence Perspective - Ndaru Satrio; Nina Zainab (Faculty of Law, Universitas Lampung, 2021)
Coordination of KPK prosecution duties as stated in Article 12A of Law no. 19 of 2019 amending Law No. 30 of 2002 concerning the Commission for the Eradication of Criminal Acts of Corruption, or Komisi Pemberantasan Korupsi (KPK) raises concerns because it creates dependence on other institutions and certainly reduces the independence of the KPK institution. As for some of the problems that need to be known from the existence of this coordination concept, among others: (1) the coordination can be directed towards the form of KPK's subordination to the prosecutor's institution; (2) coordination makes the confidentiality of data held by the KPK not maintained; (3) this coordination is very prone to conflict of interest with the prosecutor's office; (4) this coordination also raises concerns that rotten politics in the resolution of corruption cases may occur. The author uses independence principle analysis. The type of research used in compiling this paper is normative or doctrinal legal research. The research shows that coordination can be done using clear boundaries. First, coordination is still allowed to the extent that it is possible to combine cases that the KPK may not handle. Second, coordination can also be carried out in the event of merging a corruption case that is not the authority of the KPK. Third, the coordination also can be done in the case of the concurrent events. Fourth, the coordination is only related to procedural law.